Posible efecto del glifosato en el estrés oxidativo de Apis mellifera y su efecto colateral en los servicios ecosistémicos de polinización. - Manrique Torres, Oriana Valentina (Universidad Antonio Nariño, 2023)
The usage of herbicides such as glyphosate is constantly increasing for the control of weed flora. However, the toxic effect on pollinating bee populations is unknown even at sublethal concentrations. Our aim was to study the possible interaction between glyphosate and oxidative stress enzymes of Apis mellifera. Bioinformatic tools were used to study the molecular increase in Autodock Vina between glyphosate and 4 from A.